2014
DOI: 10.1097/hcr.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Detectable Change of the London Chest Activity of Daily Living Scale in Patients With COPD

Abstract: This study provided the MDC for the domains and total score of the LCADL. A change of 4 points in the total score of the LCADL can be interpreted as a meaningful change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 12 publications
0
16
2
2
Order By: Relevance
“…This result is in concordance with the original LCADL validation study and other cross-cultural validation studies which also showed high test–retest reliability. 7,1012 The minimal detectable change for LCADL total, self-care, domestic, physical, and leisure score found in the present study were slightly higher than those found in a recent study of Bisca et al 29 Our SDC values were higher which can possibly be explained by the smaller number of patients used in the Bisca et al 29 study which results in larger measurement error. The SDC% for the LCADL total score was lower than the SDC% for the domain scores.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This result is in concordance with the original LCADL validation study and other cross-cultural validation studies which also showed high test–retest reliability. 7,1012 The minimal detectable change for LCADL total, self-care, domestic, physical, and leisure score found in the present study were slightly higher than those found in a recent study of Bisca et al 29 Our SDC values were higher which can possibly be explained by the smaller number of patients used in the Bisca et al 29 study which results in larger measurement error. The SDC% for the LCADL total score was lower than the SDC% for the domain scores.…”
Section: Discussioncontrasting
confidence: 80%
“…The instrument is moderately sensitive to measure change after an intervention with improvements exceeding the recently suggested minimal detectable change. 29 The SEM values can be used to assess the relevance of observed changes in individual patients. 42 In addition, since %SDC was lowest for LCADL total, we suggest to use the LCADL total score for individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…The total score can range from 0 to 75 points, a higher score translating to greater limitations in ADL. ( 19 ) The minimal detectable change for the LCADL scale score to measure the effect of interventions is of less than 3.88 points ( 20 ) In order to assess submaximal exercise capacity, we used the six-minute walk test (6MWT). The 6MWT is a submaximal test that determines the functional capacity of patients with chronic lung disease, being easy to perform, well tolerated, reproducible, and inexpensive.…”
Section: Methodsmentioning
confidence: 99%
“…The total score can range from 0 to 75 points, a higher score translating to greater limitations in ADL. ( 19 ) The minimal detectable change for the LCADL scale score to measure the effect of interventions is of less than 3.88 points ( 20 )…”
Section: Methodsmentioning
confidence: 99%
“…A mínima diferença clinicamente importante da LCADL é de 3,88 pontos. Para seus domínios, têm-se os valores de 0,89, 2,60, 0,44 e 0,58 para cuidados pessoais, atividades domésticas, atividade física e lazer, respectivamente 19 .…”
Section: London Chest Activity Of Daily Livingunclassified